Experimental study on flue gas foam-assisted steam flooding: investigating characteristics of enhanced oil recovery and gas storage - Cao, Qiuying; Wei, Tao; Wu, Guanghuan; Yu, Jianmei; Tian, Kehan; Cao, Aiqing (Frontiers in Energy Research, 2023)
Steam flooding is one of the most widely used heavy oil thermal recovery technologies. Steam transfers heat to heavy oil to reduce viscosity and improve fluidity.The current problem is that steam loses a lot of heat in the formation, and there are serious carbon emissions in the whole production process. In this paper, flue gas and steam were combined to drive heavy oil in the form of composite thermal fluid, and foam was added on this basis. With the help of one-dimensional sandpack model, both single-model and parallel dual-model with permeability ratio experiments were conducted to investigate key characteristics such as steam heat transfer, heavy oil production and flue gas retention during the displacement process. The experimental results indicated that flue gas effectively inhibited steam condensation and reduced heat loss during the flow process. Compared to steam flooding, the sandpack model exhibited temperature rises of 4.4°C and 9.1°C at the middle and end, respectively. While flue gas foam fell slightly short of flue gas in terms of enhanced heat transfer, it outperforms in recovery factor, achieving a 10.4% improvement over flue gas-assisted steam flooding. The foam blocked gas channeling by accumulating and capturing along the flow path, resulting in a gas retention volume of 389 mL within the model. Furthermore, the flue gas foam facilitated steam flow to previously unswept lowpermeability areas, thus enhancing oil recovery. In the parallel double-model experiment, the low-permeability model exhibited significantly improved oil displacement efficiency compared to flue gas-assisted steam flooding, and the remaining oil content in the end of the high permeability model was increased by 1.9%, while the remaining oil content in the front and end of the low-permeability model was reduced by 3.5% and 3.8% respectively.